Tuning the nanostructural properties of silver nanoparticles for optimised surface enhanced Raman scattering sensing of SARS CoV-2 spike protein. (27th September 2021) - Daoudi, Kais; Ramachandran, Krithikadevi; Columbus, Soumya; Tlili, Abdelaziz; Mahfood, Mona; Khakani, My Ali El; Gaidi, Mounir
Abstract: In this work, development of fast, selective and highly sensitive sensor for detecting severe acute respiratory syndrome coronavirus 2 (known as SARS CoV-2 or COVID19) spike protein has been reported. Surface enhanced Raman spectroscopy (SERS) based direct detection of spike protein was investigated by fabricating silver nanoparticles decorated Si (AgNPs/Si) using a facile wet chemical process. Fabrication parameters such as immersion time and precursor concentration were varied; their corresponding morphological characteristics were well elucidated while assuring homogeneous decoration of AgNPs on Si substrate. Classical dye molecule such as rhodamine 6G (R6G) was utilised for the optimisation of fabricated sensor. Based on acquired intensity of R6G, the best sensor was selected, which was further employed for label free direction of spike protein. The developed sensor exhibited high sensitivity in pico-molar range with excellent reproducibility. Selectivity studies were demonstrated using DNA and H1N1 protein as well. The current findings will launch new state of art in the field of medical diagnostics.